2022
DOI: 10.1021/acs.joc.2c00321
|View full text |Cite
|
Sign up to set email alerts
|

Homolytic Aromatic Sulfonation with K2S2O5 Promoted by a Combination of Mn(OAc)3·2H2O and HFIP

Abstract: Herein, we reported a so far unprecedented Mn­(OAc)3·2H2O-promoted homolytic aromatic sulfonation. The reaction was performed under mild conditions with K2S2O5 employed as a green sulfonating reagent. Various arenes were successfully converted into desired sulfonic acids or sulfonates in high efficiency. Preliminary mechanistic studies demonstrated that the present reaction proceeds via a homolytic aromatic substitution-type mechanism involving an SO3 – radical. The combination of Mn­(OAc)3·2H2O and HFIP plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…Intriguingly, we found that the reaction of 1aa could proceed smoothly in several other solvents besides HFIP, such as DCM, MeOH, EtOH, DMSO, CH 3 COOH, and toluene (entries 5 and 6). The success of nonfluorinated solvents is in contrast with our previously reported radical sulfonation of arenes, probably attributed to a higher radical trapping ability of alkenes. Considering the solvent cost and the ease of workup, we chose DCM as the optimized solvent for the synthesis of oxindole-based sulfonates (entry 7).…”
contrasting
confidence: 90%
See 3 more Smart Citations
“…Intriguingly, we found that the reaction of 1aa could proceed smoothly in several other solvents besides HFIP, such as DCM, MeOH, EtOH, DMSO, CH 3 COOH, and toluene (entries 5 and 6). The success of nonfluorinated solvents is in contrast with our previously reported radical sulfonation of arenes, probably attributed to a higher radical trapping ability of alkenes. Considering the solvent cost and the ease of workup, we chose DCM as the optimized solvent for the synthesis of oxindole-based sulfonates (entry 7).…”
contrasting
confidence: 90%
“…Inspired by previous works, we envisioned that the SO 3 – radical could also trigger the sulfonation-cyclization cascade via a radical cyclization mechanism (Scheme D). The challenge may come from the competition between direct hyrdrosulfonation of alkenes and cyclization, which requires an ingenious substrate design.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Our methodology not only broadens the scope of synthetic applications of the SO 3 – radical as a versatile sulfonic synthon but also offers a promising strategy for the modular synthesis of sulfonyl derivatives, thereby contributing new insights and methods to the field of sulfonyl chemistry. In conjunction with our prior research efforts, , we have established a sulfonate library comprising over 100 new compounds, and further optimization and scope-expanding studies are underway in our lab.…”
Section: Discussionmentioning
confidence: 99%